Justicia Juvenil Restaurativa El nuevo paradigma (Journal on studies and research of academic knowledge, 2019)
This work is about Restorative Justice, specifically Restorative Juvenile Justice. Such an approach has become necessary considering that it is a peaceful and restorative system with a different approach in order to deal with criminal offenses. The purpose of this study was to learn about the new paradigm called Restorative Juvenile Justice, its application that places emphasis on the subjects directly affected by the commission of crimes (victim, offender and community), brief comments about its application in other countries and the review of the program carried out in our country, called: Adolescent Criminal Restorative Justice Pilot Plan, Lambaré, Paraguay. This task was accomplished through a bibliographic investigation of text analysis, laws, and the revision of the Restorative Program that was carried out in the Republic of Paraguay. The investigation showed that Restorative Juvenile Justice has achieved positive results in its application and a wide acceptance as a means to face the crimescommitted by adolescent offenders.
Keywords: Restorative Justice; Violating teenager; Criminal law